Agricultural Research Trends of Agricultural Faculties in Turkey: Bibliometric Analysis of Publications Between 1996- 2011 in Life Sciences Database - Besimoğlu, Can (Information World, 2015)
Examination and analysis of scientific research provides evaluation about new knowledge production, solving problems, creating innovation and R&D activities on science and technology areas of countries. In this research, subject covarege of the publications of agricultural faculties in Turkey listed on Life Sciences Database (YBVT) between 1996 and 2011 are analysed. In addition to that agricultural information structure and emerging trends are visuliazed with the social network analysis. With the subject analysis, whether the conducted research was compatible with the desired level of research regarding the emphasis and priorities in policies located in important documents like State Planning Organisation development plans, The Ministry of Food, Agriculture and Livestock strategy documents, The Scientific and Technological Research Council of Turkey (TÜBİTAK) meeting decisions/proceedings, TÜBİTAK Vision 2023 Food and Agriculture Panel, TÜBİTAK Public Agriculture Research Program etc. is tried to be identified. When we compare policies with the faculty of agriculture publicaitons, such as animal resources, plant breeding and genetics, organic agriculture, genotypes are researched constantly. In order to direct stated other policies to the research, State Planing Organization, The Ministry of Food, Agriculture and Livestock, TÜBİTAK, Supreme Council for Science and Technology cooperate with universities authorities and activate human resources, support and incentive funds more efficiently.
Keywords: Bibliometrics; social network analysis; agricultural research policies; keyword cooccurance; agricultural research trends